2023
DOI: 10.1108/ebhrm-11-2022-0267
|View full text |Cite
|
Sign up to set email alerts
|

Quick-witted entrepreneurs versus systematic managers: a comparative analysis of decision-making competence

Francesco Tommasi,
Riccardo Sartori,
Sara Bollarino
et al.

Abstract: PurposeDecision-making competence (DMC) of entrepreneurs and managers is a longstanding topic in this increasingly globalized world. These figures operate in conditions not within their own control, and good levels of DMC are often considered to be desirable for the flourishing of business and society. This paper reports an empirical investigation on the DMC of entrepreneurs and managers, in an attempt to inform about their tendencies to incur in risky and costly choices.Design/methodology/approachThree cognit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 56 publications
0
1
0
Order By: Relevance
“…Another recent study ( Tommasi et al, 2023 ) explored the presence of bias in professionals and demonstrated that entrepreneurs exhibit higher levels of under/overconfidence (i.e., self-confidence in taking decisions) than managers and specifically showed a marked presence of this bias among entrepreneurs at younger ages. Therefore, both higher levels of expertise and seniority in terms of age require thorough investigation in the context of resistance to decision biases.…”
Section: Discussionmentioning
confidence: 99%
“…Another recent study ( Tommasi et al, 2023 ) explored the presence of bias in professionals and demonstrated that entrepreneurs exhibit higher levels of under/overconfidence (i.e., self-confidence in taking decisions) than managers and specifically showed a marked presence of this bias among entrepreneurs at younger ages. Therefore, both higher levels of expertise and seniority in terms of age require thorough investigation in the context of resistance to decision biases.…”
Section: Discussionmentioning
confidence: 99%